P-98 LACTATE/ALBUMIN RATIO AS A MARKER OF MORTALITY IN PATIENTS HOSPITALIZED WITH ACUTE ON CHRONIC LIVER FAILURE IN A MEXICAN HOSPITAL: CLINICAL ANALYSIS AND PERSPECTIVES - Gabriela Bretón Arroy; Lucia Amairani Robles Casanova; Moises Coutiño Flores; María Del Rosario Herrero Maceda; Scherezada María Isabel Mejia Loza (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Albumin and lactate are markers of systemic inflammation, which are altered by their hepatic metabolism; however, they can be useful indicators of mortality in patients with cirrhosis. This study aimed to determine the association between lactate/albumin ratio levels and mortality in patients with ACLF. Patients / Materials and Methods: A retrospective and observational cohort study was conducted. Eighty-five patients diagnosed with ACLF according to the EASL-CLIF criteria were included from February 2022 to May 2024. Patients with hepatocellular carcinoma were excluded.Data analysis was performed using GraphPad Prism version 10.2.3 and Microsoft Excel software. An ROC curve was performed to establish the cutoff point of the lactate/albumin ratio, as well as determine the sensitivity and specificity of the model to predict 28-day mortality. Results and Discussion: Eighty-five patients were included, 68 (80%) men and 17 (20%) women; average age 52.4 years (39 -80). Alcohol consumption was the main cause of cirrhosis in 74 (87.05%), autoimmune diseases in 7 (8.23%), and MASLD in 4 (4.70%) (Table 1). 12 patients (14.11%) had ACLF grade 1, 29 (34.11%) grade 2 and 44 (51.76%) grade 3. With failure: kidney 61 (71.76%), liver 57 (67.05%), brain 49 (57.64%), coagulation 37 (43.52%), respiratory 15 (17.64%) and circulatory 5 (5.88%) (Table 1). 37 (43.52%) died within the first 28 days. The cutoff point of the lactate/albumin ratio was 1.74 (AUC 0.87), with a p value <0.0001, sensitivity 71.7% and specificity 58.8% (95% CI) (Figure 1). Conclusions: The cutoff point of the lactate/albumin ratio of 1.74 allows for the objective prediction of mortality in patients with ACLF using easily accessible laboratory tests.